2023
DOI: 10.1039/d3cp02205f
|View full text |Cite
|
Sign up to set email alerts
|

Potential of nanostructured carbon materials for iodine detection in realistic environments revealed by first-principles calculations

Kazem Zhour,
Ayoub Daouli,
Andrei Postnikov
et al.

Abstract: In the context of effective detection of iodine species (I2, CH3I) formed in nuclear power plants and nuclear fuel reprocessing facilities, we perform a comparative study of potential sensing performance of 8-Pmmn borophene, BC3, C3N, and BC6N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Indeed, these gases are widely present on the surfaces of layered materials and can alter their functional properties. 24–33 First-principles calculations have shown that 2D materials such as group V 2D pnictogens, 34,35 layered transition-metal dichalcogenides, 36 BCP, 37,38 β-TeO 2 monolayer, 39 and InSe-like phosphorus carbide 40 exhibit an exceptional selectivity to NO 2 molecules and are promising for application in gas sensors for nitrogen-containing gases. Another theoretical work has shown that the work function of metal-doped hexagonal boron nitride can be tuned by adsorption of NO 2 and NH 3 molecules, making metal-doped hexagonal boron nitride a promising material for monitoring these gases.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these gases are widely present on the surfaces of layered materials and can alter their functional properties. 24–33 First-principles calculations have shown that 2D materials such as group V 2D pnictogens, 34,35 layered transition-metal dichalcogenides, 36 BCP, 37,38 β-TeO 2 monolayer, 39 and InSe-like phosphorus carbide 40 exhibit an exceptional selectivity to NO 2 molecules and are promising for application in gas sensors for nitrogen-containing gases. Another theoretical work has shown that the work function of metal-doped hexagonal boron nitride can be tuned by adsorption of NO 2 and NH 3 molecules, making metal-doped hexagonal boron nitride a promising material for monitoring these gases.…”
Section: Introductionmentioning
confidence: 99%